1996
DOI: 10.2105/ajph.86.10.1410
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with emergency department visits by children with asthma: implications for health education.

Abstract: OBJECTIVES: This study investigated the relationship between psychosocial and behavioral factors and the frequency of emergency department visits for childhood asthma. METHODS: Data obtained from a survey of parents of 445 children who were being treated for asthma in the emergency room of a large urban hospital were examined. RESULTS: Factors associated with high emergency department use included the child's being of younger age, a greater number of days with symptoms of asthma, a higher number of asthma medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 17 publications
4
61
1
1
Order By: Relevance
“…The literature suggests that 25% of pediatric ED visits may be from chronic users of the ED. 9 However, for the purpose of this study, the number of patients that had repeat visits was less important than independent encounters. The paradigm for treatment by ED physicians currently presumes no continuity of care within that setting; thus, each encounter is approached and treated independently.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The literature suggests that 25% of pediatric ED visits may be from chronic users of the ED. 9 However, for the purpose of this study, the number of patients that had repeat visits was less important than independent encounters. The paradigm for treatment by ED physicians currently presumes no continuity of care within that setting; thus, each encounter is approached and treated independently.…”
Section: Discussionmentioning
confidence: 93%
“…6,7 One recent study found that many parents of children with asthma could identify a primary care provider (PCP) but preferred to use the ED for asthma care because they perceived asthma as a disorder that should be treated as an emergency. 8 There is evidence that children with asthma present to the ED repeatedly 9 ; several published surveys suggest that at least 25% of such patients may be chronic users of the ED for primary asthma care, multiple acute episodes, or repeated visits during 1 exacerbation. 7,8 Overall, 30% of children treated for asthma in EDs require admission to the hospital.…”
Section: Methodmentioning
confidence: 99%
“…However, like most other studies, we found that a high proportion of these children exhibited health care-utilization patterns that suggest more severe or uncontrolled asthma; 25% had been hospitalized in the last year, and 60% had at least 1 prior ED visit for asthma in the last year. This apparent disconnect between the underlying asthma severity and the high rates of past ED visits and hospitalizations may be a reflection of the inability to accurately measure underlying asthma severity or the fact that health care-utilization patterns are driven in large part by behavioral and psychosocial factors 7,12 rather than disease-specific measures such as asthma severity and control. Another interesting and paradoxical finding with respect to the high frequency of past ED use in this population was that only 5% reported that the ED was their usual source of asthma care.…”
Section: Discussionmentioning
confidence: 99%
“…2 ED use for asthma care in children has been associated with many factors including younger age, gender, minority status, poverty, living in an urban area, having Medicaid or lack of insurance, access to care, quality of care, allergen-prone environments, and poorer health. [6][7][8][9][10][11][12] However, the vast majority of these studies have been conducted in the inner-city environments of very large urban centers. There is less known about whether the characteristics of children who visit EDs in more suburban and rural settings differ from those of their urban counterparts.…”
mentioning
confidence: 99%
“…5,6,15 Wasilewski et al 15 observaram que crianças com hospitalização prévia por asma apresentavam alto risco de utilizar serviços de emergência. Sua conclusão foi que famílias usando freqüentemente serviços de emergência necessitam de educação sobre asma.…”
Section: Discussionunclassified